Sports Medicine Fellowship Training Significantly Increases Sports Case Volume: An Analysis of ACGME Case Log Data from 2006 to 2019 - Ayooluwa T. Ibitayo, B.S; Nisha N. Kale, B.A; Cadence Miskimin, M.S; Mary K. Mulcahey, M.D (Elsevier, 2021)
Purpose: The purpose of this study was to determine the experiential benefit of completing a sports medicine fellowship for orthopaedic surgeons specializing in the treatment of sports injuries. Methods: Accreditation Council for Graduate Medical Education case logs were examined for sports medicine cases performed by orthopaedic surgery residents from 2006 to 2019 and for orthopaedic sports medicine fellows from 2010 to 2019. The average number of arthroscopic cases was evaluated for residents and fellows according to each body group. Additional data based on subcategorization of arthroscopic cases was analyzed as well. A Student t-test was conducted to compare the means between the groups. Results: Orthopaedic sports medicine fellows reported 274.9% more shoulder (260.6 ± 77.31 vs 94.8 ± 23.7, P < .0001), 685.6% more humerus/elbow (17.1 ± 6.14 vs 2.5 ± .508, P < .0001), 596.7% more pelvis/hip (41.4 ± 25.40 vs 6.9 ± 2.97, P < .0001), 188.1% more femur/knee (281.4 ± 57.85 vs 149.6 ± 34.09, P < .0001), and 264.1% more foot/ankle (16.9 ± 5.58 vs 6.4 ± .600, P < .0001) sports cases compared to orthopaedic surgery residents. Orthopaedic sports medicine fellows performed significantly more shoulder arthroscopy cases (126.8 ± 3.96 vs 86.0 ± 22.26, P = .032) and knee arthroscopy cases (179.4 ± 8.98 vs 101.75 ± 33.51, P = .015) than residents over a 5-year period. Conclusions: On average, orthopaedic sports medicine fellowships significantly increase sports case volume of orthopaedic trainees, especially in the upper extremity. Notable increases were in the shoulder, femur/knee, and pelvis/hip. We have demonstrated that orthopaedic sports medicine fellowships significantly increase exposure to sports medicine related cases. Clinical Relevance: It is important for case volume to be evaluated across orthopaedic sports medicine fellowships because they must ensure that fellows receive adequate training in orthopaedic sports medicine.